Perceiving violence against healthcare workers in a child and adolescent emergency psychiatric ward in Hungary: a qualitative pilot study - Gyula Sófi; Krisztina Törő; Gábor Csikós; Gergely Fliegauf; Gergely Fliegauf (Frontiers in Psychology, 2023)
AimPsychiatry is a challenging setting that requires extraordinary effort from the staff. Healthcare workers in the field of psychiatry face substantial levels of violence, making the identification of abuse risk factors a social concern. Both the conduct of the children and their relatives can pose potential harm. Our study delved into the criminological and psychiatric factors underlying violence against healthcare workers.MethodologyWe used qualitative, semi-structured, self-developed, online questionnaire involving 21 respondents. The participants were representing the staff composition of our department. The data set was coded in two phases using a multi-stage content analysis method. The results were compared with Hungarian and international literature.FindingsAmong the participants, 52% reported no instances of physical abuse. The most prevalent form of perceived non-contact abuse was threats, accounting for 38% of reported cases. The identified risk factors for abuse included the child’s psychiatric disorder, communication issues, parental behavior, and low socio-economic status. Psychological trauma was identified as the most severe consequence. The respondents’ opinion indicated that the most common cause of violence (52%) was attributed to the child’s mental disorder. Workers primarily deal with abuse through negative emotions, with 76% of them reporting feelings of victimization. Additionally, 43% believed that abuse cannot be avoided, while 19% emphasized the significance of worker competence.ValueOur research can help to identify risk factors in child psychiatry wards and provide guidance for developing effective responses to violence against healthcare workers in Hungary, especially at our ward.